Front Cover: Phytometabolite profiling of Coronil, a herbal medicine for COVID‐19, its identification by mass‐spectroscopy and quality validation on liquid chromatographic platforms. Issue 22 (19th November 2021) - Balkrishna, Acharya; Tomer, Meenu; Verma, Sudeep; Joshi, Monali; Sharma, Priyanka; Srivastava, Jyotish; Varshney, Anurag
Abstract : DOI: 10.1002/jssc.202100499 The cover picture shows schematics for analytical techniques used in determination of phyto‐metabolites in Coronil, a tri‐herbal medicine for COVID‐19. Mass Spectrometry coupled with Quadrapole Time of Flight (MS‐QToF) was applied for screening of the compounds ( Lower left panel ). Selected Analytes were quantified on HPLC and High‐Performance Thin‐Layer Chromatography (HPTLC) ( lower middle, right panels ), with accuracy and precision. Background image shows perspective view of comparative HPLC profiles of 15 different batches of Coronil. These methods and data define the analytical purity of Coronil, and scientifically validate its quality control evaluation.